The nature of the CM parent asteroid regolith based on cosmic ray exposure ages. (30th September 2020) - Zolensky, Michael E.; Takenouchi, Atsushi; Mikouchi, Takashi; Gregory, Timothy; Nishiizumi, Kunihiko; Caffee, Marc W.; Velbel, Michael A.; Ross, Daniel K.; Zolensky, Andrew; Le, Loan; Imae, Naoya; Yamaguchi, Akira
Abstract: Cosmic ray exposure (CRE) ages of CM chondrites have been found to have multiple peaks (as many as four), in stark contrast to other groups of chondrites (Nishiizumi and Caffee 2012; Herzog and Caffee 2014). In this study, we sought correlations between the CRE ages and petrography of CM chondrites, and we conclude that the degree of aqueous alteration does appear to vary with the CRE ages—the CMs displaying the most aqueous alteration all have relatively short exposure ages. However, some CMs with low degrees of alteration also have short exposure ages—thus, this apparent correlation is not exclusive. We also found a definite inverse relation between the number of distinctive lithologies in a CM and its exposure age, which could indicate different responses of homogeneous and heterogeneous meteoroids to the space environment between their onset of exposure (exhumation and ejection from the parent body) and arrival at Earth. Breccias have more internal surfaces of lithologic discontinuity, possibly resulting in weaker meteoroids that disintegrate more readily than their more homogeneous counterparts. Our results suggest that CM chondrite regoliths consist of numerous genomict lithologies in a breccia with millimeter‐ to decimeter‐scale clasts, with varying degree of heating/metamorphism.